LACHESIS restricts gametic cell fate in the female gametophyte of Arabidopsis. - Rita Gross-Hardt; Christina Kägi; Nadine Baumann; James M Moore; Ramamurthy Baskar; Wendy B Gagliano; Gerd Jürgens; Ueli Grossniklaus (PLoS Biology, 2007)
In flowering plants, the egg and sperm cells form within haploid gametophytes. The female gametophyte of Arabidopsis consists of two gametic cells, the egg cell and the central cell, which are flanked by five accessory cells. Both gametic and accessory cells are vital for fertilization; however, the mechanisms that underlie the formation of accessory versus gametic cell fate are unknown. In a screen for regulators of egg cell fate, we isolated the lachesis (lis) mutant which forms supernumerary egg cells. In lis mutants, accessory cells differentiate gametic cell fate, indicating that LIS is involved in a mechanism that prevents accessory cells from adopting gametic cell fate. The temporal and spatial pattern of LIS expression suggests that this mechanism is generated in gametic cells. LIS is homologous to the yeast splicing factor PRP4, indicating that components of the splice apparatus participate in cell fate decisions.